Evaluation and Effectiveness of River Training Works with Special Focus on Tinau River in Rupandehi District of Nepal - Dahal, Khet Raj; Bhusal, Bhesh Raj (Journal of Lumbini Engineering College, 2022)
Flood in Tinau River is very common since past decades. It has damaged several houses, cultivated land and live stocks in the past and continues till the date. Hundreds of hectares of cultivated lands have been deposited with sand and debris making the land unsuitable for farming. The governments of Nepal and local bodies have been launching projects for flood control. Various types of structures were built in the past. Millions of Nepalese Rupees have been invested for river training works. However, the river training works is not functioning well. This study was conducted during the period from March 2019 to April 2020. The objective of this study is to evaluation the effectiveness of river training works with especial focus on Tinau River in Rupandehi district of Nepal. Field observation, in-depth interview, focus group discussion and questionnaire survey were the major tools used for the field investigation. The study found that the extraction of river bed materials and unmanaged catchment area are also the causes of the ineffectiveness of the river training works. It also includes lack of monitoring and supervision, socio-political pressure and lack of enforcement of law and policies. Similarly, some other causes are inadequate co-ordination between line agencies, inadequate plan and policies and lack of awareness are the minor causes of ineffective river training works. Furthermore, inadequate maintenance of built up structures, irresponsible of beneficiary group, unmanaged population growth at catchment area were also found causes behind sustainability of the river training works. The study would like to suggest that the river bed extraction should be conducted in a balanced way. And, hydrological, geological and geotechnical studies should be conducted in detail before design of the river training structures.